Potential Underuse, Overuse and Inappropriate Use of Antidepressants in Older Veteran Nursing Home Patients - Hanlon, Joseph T. (2011)
OBJECTIVE: To examine prevalence and patient/site level factors associated with potential underuse, overuse and inappropriate use of antidepressants in older Veterans Affairs (VA) Community Living Center (CLC) patients. DESIGN: Longitudinal study. SETTINGS: 133 VA CLCs. PATIENTS: 3,692 veterans 65 years or older admitted between 1/1/04-6/3/05 with long stays (90+days). MEASUREMENTS: Prevalence of potential underuse, inappropriate use and overuse of antidepressants in patients with and without depression (as documented by International Classification of Diseases-9 Clinical Modification codes or Depression Rating Scale). RESULTS: Selective serotonin reuptake inhibitors were the most commonly prescribed antidepressant. Of the 877 patients with depression, 25.4% did not receive an antidepressant suggesting potential underuse. Among depressed patients who received antidepressants, 43.1% had potential inappropriate use due primarily to problems seen with drug-drug and drug-disease interactions. Of the 2,815 patients who did not have depression, 1190 (42.3%) were prescribed one or more antidepressants; of these only 48 of 1190 (4.0%) had a FDA-approved labeled indication-suggesting potential overuse. Overall only 17.6% of antidepressant use was appropriate (324/1844). The only consistent patient factor associated with potential underuse and overuse use was taking an antipsychotic without evidence of schizophrenia (underuse-adjusted relative risk ratio [ARRR] 0.56, 95% confidence interval [CI] 0.33-0.94; overuse-Adjusted Odds Ratio 1.52, 95% CI 1.21-1.91). Both having moderate/severe pain (ARRR 1.54, 95% CI 1.08-2.20) and the prescribing of an anxiolytic/hypnotic (ARR 1.33, 95% CI 1.02-1.74) increased the risk of potential inappropriate antidepressant use. CONCLUSION: Potential problems with the use of antidepressants were frequently observed in older US veteran CLC patients. Future studies are needed to examine the true risks and benefits of antidepressant use in CLC and non-VA nursing homes.